2020
DOI: 10.3750/aiep/02939
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of brown trout, Salmo trutta (Actinopterygii: Salmoniformes: Salmonidae), in the Danube River basin of Croatia revealed by mitochondrial DNA

Abstract: Background. The molecular diversity of brown trout, Salmo trutta Linnaeus, 1758, has been poorly studied in Croatia. The control region of mitochondrial DNA (CR mtDNA) is in addition to other molecular markers a reliable for identifying phylogenetic lineages (haplogroups) and haplotypes of brown trout. Based on analyses of the control region of mitochondrial DNA several major brown trout phylogenetic lineages were identified of which the Danubian (DA) haplotypes, though not all, are considered native to Croati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…In future study, the inclusion of landmarks to examine the lower jaw and head depth could give additional insight into the ecologies of the lineages, as head morphology can reflect trophic variation (Wainwright et al, 1991;Piggott et al, 2018), and these additional landmarks could better explain the largest Procrustes variation within the Atlantic lineage. Kanjuh et al (2020) found that none of the sampled streams included in this study contained completely pure Danube trout lineage populations, with at least one hybrid or Atlantic lineage individual with Atlantic trout lineage genes detected at each site. The present study indicated a difference in shape between trout belonging to the Danubian and Atlantic lineages.…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…In future study, the inclusion of landmarks to examine the lower jaw and head depth could give additional insight into the ecologies of the lineages, as head morphology can reflect trophic variation (Wainwright et al, 1991;Piggott et al, 2018), and these additional landmarks could better explain the largest Procrustes variation within the Atlantic lineage. Kanjuh et al (2020) found that none of the sampled streams included in this study contained completely pure Danube trout lineage populations, with at least one hybrid or Atlantic lineage individual with Atlantic trout lineage genes detected at each site. The present study indicated a difference in shape between trout belonging to the Danubian and Atlantic lineages.…”
Section: Discussionmentioning
confidence: 78%
“…This lower variation in body height could be additional proof of the influence of fish farm origin on the shape of all Atlantic specimens in this study. The hybrids analysed here share genes with Danubian trout (Kanjuh et al, 2020), and moreover they hatched and evolved in the same habitats as pure Danubian trout. As such, adaptations to the same habitats could be similar due to their high phenotypic plasticity, explaining why the shape of hybrids did not differ significantly from the shape of pure Danubian populations.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations